Coupled heat and moisture transfer modeling of a PCM–desiccant wall panel for indoor temperature and humidity control: A one-dimensional hygrothermal approach - Abdulwahab A. Alnaqi; Jalal Alsarraf; Abdullah A.A.A. Al-Rashed (Energy and Buildings, 2026)

Comparative thermo-environ-economic analysis of solar-assisted and conventional ejector-compression heat pump systems for space heating - Jalal Alsarraf; Abdulwahab A. Alnaqi; Abdullah A.A.A. Al-Rashed (Energy and Buildings, 2026)

Geometric optimization of a turbulator in nanofluid flow around a bundle of nuclear reactor fuel rods using the response surface methodology - Jalal Alsarraf; Abdulwahab A. Alnaqi; Abdullah A.A.A. Al-Rashed (Annals of Nuclear Energy, 2025)

Sensitivity analysis of parameters and optimization of produced entropy in a nuclear reactor with equilateral fuel rod arrangement and variable angle turbulators - Abdullah A.A.A. Al-Rashed; Abdulwahab A. Alnaqi; Jalal Alsarraf (Annals of Nuclear Energy, 2025)

Numerical investigation of the geometric parameters effect of helical blades installed on horizontal geo heat exchanger - Abdulwahab A. Alnaqi; Abdullah A.A.A. Al-Rashed; Jalal Alsarraf (Geothermics, 2025)

The waste heat of a biofuel-powered SOFC for green hydrogen production using thermochemical cycle; Economic, environmental analysis, and tri-criteria optimization - Abdulwahab A. Alnaqi; Jalal Alsarraf; Abdullah A.A.A. Al-Rashed (Fuel, 2023)

A comparative investigation of syngas and biofuel power and hydrogen plant combining nanomaterial-supported solid oxide fuel cell with vanadium-chlorine thermochemical cycle - Abdullah A.A.A. Al-Rashed; Jalal Alsarraf; Abdulwahab A. Alnaqi (Fuel, 2023)

Functionalized multi-walled carbon nanotubes for oil spill cleanup from water - Thamer Adnan Abdullah; Tatjana Juzsakova; Sanaa A. Hafad; Rashed Taleb Rasheed; Noor Al-Jammal; Muhammad Ali Mallah; Ali Dawood Salman; P. C. Le; Endre Domokos; Mustafa Aldulaimi (Clean Technologies and Environmental Policy, 2022)
The growing global economy resulted in an incessant increase in transportation and exploitation of oil. Hence, the oil spillage has been considered a serious threat to aquatic and terrestrial ecosystems. Therefore, water purification has been considered a major challenge around the world. There are numerous classical methods available for oil removal from water, but owing to multiple defects and disadvantages, research efforts have focused to find such adsorbents which can improve oil adsorption capability. Traditional adsorbent material typically applied in oil removal includes activated carbon, organoclays, wool, zeolites, etc. These materials suffer from several drawbacks such as low absorption capacity, non-selective absorption, and complicated reusability, whereas nano-adsorbents offer multiple advantages such as having multiple sorption sites, large surface area, short intra-particle diffusion distance, tuneable pore size, and ease of low-temperature modification. Multi-walled carbon nanotubes (MWCNTs) are extensively used adsorbent materials with a strong affinity for the removal of organic pollutants. The functionalization MWCNTs further increase the sorption capacity of adsorbents manifolds to remove organic materials. These nanocomposites are also compatible with green materials and considered environmentally friendly adsorbents. This review paper aims at providing an insight to understand the properties of the MWCNTs and their potential use to adsorb hydrocarbons from water. Moreover, the synthesis methods of those materials, their modification procedures including the functionalization with metal oxide nanoparticles, and applications are also discussed in detail. Graphic abstract

Conjugate Heat Transfer in an Annulus with Porous Medium Fixed Between Solids - Irfan Anjum Badruddin; Salman Ahmed N. J.; Abdullah A. A. A. Al-Rashed; N. Nik-Ghazali; Mohammed Jameel; Sarfaraz Kamangar; H. M. T. Khaleed; T. M. Yunus Khan (Transport in Porous Media, 2015)

Analysis of Heat and Mass Transfer in a Vertical Annular Porous Cylinder Using FEM - Irfan Anjum Badruddin; N. J. Salman Ahmed; Abdullah A. A. A. Al-Rashed; Jeevan Kanesan; Sarfaraz Kamangar; H. M. T. Khaleed (Transport in Porous Media, 2012)